The Level of Wisdom of Pre-service Counselors in Providing Guidance and Counseling Services - Kartika Sari, Widya; Sulusyawati , Heni; Dwi Krisphianti , Yuanita; Barida , Muya; Ari Widyastuti , Dian; Supriyanto , Agus (Corolla International Conference, 2025)
This study aimed to describe the level of wisdom among pre-service counselors in providing guidance and counseling services, categorized into three levels: high, medium, and low. A quantitative descriptive design was employed involving 253 students majoring in Guidance and Counseling from universities located in Bengkulu, East Java, Yogyakarta, and Central Java. The Wisdom Character Scale (WCS) was utilized as the research instrument, comprising 84 valid and reliable items with a Cronbach’s Alpha coefficient of 0.94. The scale was developed based on six key dimensions: social behavior, decision-making, emotional stability, self-reflection, tolerance, and assertiveness. The findings revealed that 13.83% of participants were categorized as having low levels of wisdom, 69.57% demonstrated medium levels, and 16.60% were classified as high. These results indicate that the majority of pre-service counselors exhibit moderate levels of wisdom, suggesting that they have acquired the foundational elements of wise conduct such as empathy, ethical reasoning, and interpersonal sensitivity. However, further development is needed in areas requiring deeper self-reflection and emotionally balanced decision-making. Overall, the results underscore the importance of embedding structured educational and reflective training programs into counselor education curricula to strengthen the wisdom dimension as an essential professional competency. Such integration would promote not only cognitive and affective growth but also the cultivation of ethical judgment and reflective understanding essential for effective counseling practice.